Connection between body posture indicators and dominant hand with scoliotic body posture in handball players - Vedrana Grbavac; Martina Rezić; Ivana Čerkez Zovko (University of Banja Luka, Faculty of physical education and sport, 2018)
The modern way of life is the cause of the increasing occurrence of improper body posture in children and adolescents. In athletes, improper body posture can lead to numerous chronic health problems and injuries that affect their performance in sports. The handball game is characterized by dynamism and mobility, with constant and rapid changes of body positions and technique elements. Due to certain characteristics of handball as a sport (parts of the technique that are asymmetric due to playing with one hand) there is a reasonable doubt that handball players are exposed to factors that can cause a development of postural deformities. The aim of the study is to investigate whether scoliotic posture is a frequent occurrence in adolescents who train handball, and whether there is a correlation between the relevant indicators of improper body posture and the dominant hand with scoliotic body posture in handball players. The study was conducted on a sample of 98 adolescents aged 13-18 who had been involved in the training process for over three years and were tested with clinical Adams forward bend test. A posterior examination was used to determine the types of body posture. The sample of variables for the assessment of body posture contained numerical values ​​of eight reference points in the posterior examination. To determine the differences between groups in variables of the questionnaire, and in determining the difference between the respondents in the variables obtained from the questionnaire, the Chi-square test was used, and a contingency table with frequencies and percentages was determined. A significant difference was found between right-sided and normal body posture, where right-sided posture subjects spent significantly more years training a handball compared to those with normal body posture, which suggests that this sport can be associated with the occurrence of a scoliotic posture.